Fabrication of single-mode circular optofluidic waveguides in fused silica using femtosecond laser microfabrication. (September 2021) - Liu, Zhengming; Xu, Jian; Lin, Zijie; Qi, Jia; Li, Xiaolong; Zhang, Aodong; Lin, Jintian; Chen, Jianfang; Fang, Zhiwei; Song, Yunpeng; Chu, Wei; Cheng, Ya
Highlights: Centimeter-length glass microchannels with the diameters of ~10 µm are fabricated. Diameters of microchannels can be flexibly tuned by slit width and focusing optics. Centimeter-length single-mode optofluidic waveguides inside glass are demonstrated. Abstract: We demonstrate fabrication of single-mode circular optofluidic waveguides in fused silica glass substrates using femtosecond (fs) laser assisted chemical etching based on slit beam shaping. The fabrication procedure consists of four steps: slit-assisted fs laser direct writing of fused silica, selective chemical etching, polydimethylsiloxane film bonding, and vacuum-assisted liquid filling. The combination of slit beam shaping and high numerical aperture objectives ensures very narrowly modified lines with nearly circular cross-sections during laser direct writing. Introduction of a string of extra-access ports allows production of uniform circular microchannels with the diameters of ~10 µm and the lengths at the centimeter scale due to the improvement of wet chemical etching process. By vacuum-assisted filling a mixture of liquid paraffin and decane into a microchannel structure, a single-mode circular optofluidic waveguide embedded in glass can be obtained.